Pleiotropic effects of growth hormone signaling in aging - Bartke, Andrzej (Trends Endocrinol Metab, 2011)
Growth hormone (GH) affects somatic growth, sexual maturation, body composition and metabolism, as well as aging and longevity. Mice lacking GH or GH receptor outlive their normal siblings and exhibit symptoms of delayed aging associated with improved insulin signaling and increased stress resistance. Beneficial effects of eliminating the actions of GH are counterintuitive but conform to the concept of antagonistic pleiotropy. Evolutionary selection for traits promoting early life fitness and reproductive success may account for detrimental effects post-reproductively. Reciprocal relationships between GH signaling and longevity discovered in mutant mice apply also to normal mice, other mammalian species, and perhaps humans. This review summarizes the present understanding of the multifaceted relationship between somatotropic signaling and mammalian aging.